Digital Preaching in HIV/AIDS Prevention: An Analysis of Engagement on @victoryplus.yogyakarta - Achmad Dzikri Fanshabi; Andi Faisal Bakti (Warta Ikatan Sarjana Komunikasi Indonesia, 2026)
This study examines a local case of HIV/AIDS prevention and stigma reduction in Yogyakarta, Indonesia, focusing on the role of the Victory Plus Yogyakarta Foundation in integrating social and religious approaches. HIV/AIDS prevention programs in Indonesia continue to face major challenges, including unequal access to health services, social inequality, and persistent stigma against people living with HIV/AIDS (PLWHA). This study aims to analyze the role of religious leaders in HIV/AIDS prevention from both global and local perspectives, as well as the role of religious leadership within the Victory Plus Yogyakarta Foundation. Employing a constructivist paradigm and a qualitative approach, the research uses in-depth interviews, literature reviews, and data and source triangulation. The theoretical framework is based on Jan Servaes’ development communication perspective, which emphasizes the interaction between global and local dimensions and the importance of participatory social actors. The study is further enriched by Patchanee Malikhao’s perspective on the strategic role of religious leaders in health communication. The findings show that HIV/AIDS prevention efforts continue to encounter barriers such as limited public participation, unequal access to services, and persistent stigma toward PLWHA. Nevertheless, the digital da'wah communication approach implemented by the Victory Plus Yogyakarta Foundation has proven effective in increasing public awareness, reducing stigma, and encouraging empathy and social acceptance. Religious leaders play a strategic role in communicating humanistic moral values, although capacity-building remains necessary to prevent the reproduction of stigmatizing narratives. This study contributes theoretically by integrating Jan Servaes’ participatory development communication framework with Patchanee Malikhao’s faith-based health communication perspective, offering a new perspective on inclusive and culturally grounded HIV/AIDS communication strategies in local religious communities.